Elementary School Students’ Perception of Online Learning During COVID-19 Pandemic - Mujiyatun Mujiyatun (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aimed to investigate the students’ perception of online learning in Islamic religious education learning during COVID-19 Pandemic. This research method uses a quantitative. The data were collected through a questionnaire distributed by the researcher using Google Forms. The respondents of this study were 70 students in grade 6 of elementary school. The data were analyzed by using interpretation guidelines. This study found that students' perceptions of online learning by using digital-based applications were categorized as good in terms of material understanding, teaching materials, student competencies, barriers, parental support, and school support. The most frequently used teaching materials were printed books, e-books, PowerPoint, and games. At the same time, the most commonly used applications were WhatsApp, Google Meet, Zoom, and Google Classroom. Thus, using digital-based applications gets a good response from students who can make online learning more effective.